Relationship between General Health and Musculoskeletal Discomfort along with Psychosomatic Complaints in Nurses - Majid Mesgartehrani; Mahin Kakolarimi; Dariush D Farhud; Maryam Shabany; Zainab Mesgartehrani; Dariush Norozian; Mohammad Mesgartehrani (Tehran University of Medical Sciences, 2022)
Background: Workplace problems can lead to psychosomatic complaints. We aimed to assess the relationship between general health and occurrence of musculoskeletal disorders along with psychosomatic complaints. Methods: This was a cross-sectional study.  This research was conducted about the nurses who worked at the hospitals located in the northwest of Tehran, Iran (Valiasr, Farhikhtegan, and Khatam), and participated in this study from Aug 2019 to Feb 2020. The data were collected by the demographic and clinical information questionnaire. Goldberg's general health questionnaire and psychosomatic complaint scale were completed by nurses. Results: In total, 158 nurses participated in this study. There was a significant relationship between the score of the general health questionnaire (GHQ) and psychosomatic complaints in three categories (low, moderate, and high) (P≤0.0001). There was a significant relationship between the mean score of GHQ and musculoskeletal discomfort in the neck, shoulder, forearm, hand and wrist, upper/lower back, knee, and ankle (P≤0.0001). Conclusion: Continuity of psychosomatic complaints may be a risk factor for mental health in nurses and may affect the quality of care. Hence, health policymakers and hospital managers should consider it in service training for nurses.